Coagulopathies in novel coronavirus (SARS-CoV-2) pandemic: emerging evi- dence for hematologists (2020)
The coronavirus disease (COVID-19), which is also known as acute respiratory syndrome coronavirus-2 (SARS-CoV2) is a transmissible disease, has phenotypes varying from asymptomatic to Acute Respiratory Distress Syndrome (ARDS) or multiple organ dysfunction syndrome (MODS) and ultimately death in certain cases. Coagulation disorders are being frequently reported amongst these patients and the pathogenesis is still not completely understood. Proposed mechanisms for these coagulopathies comprise a hypercoagulable state with microand/or macro- thrombosis in the vessels. A number of changes have been reported or proposed in circulating prothrombotic factors in COVID-19 patients and includes elevation in both factor VIII and fibrinogen, circulating prothrombotic microparticles and hyperviscosity. The COVID-19 patients are showing varied coagulopathies and are at high risk for venous thromboembolism (VTE) which demands an early intervention. This paper reviews the evolving data regarding the evaluation and managing of coagulopathies in patients with COVID-19.